Antiepileptic drugs and the fetal epigenome. Issue 1 (27th September 2012) - Emes, Richard D.; Clifford, Harry; Haworth, Kim E.; Farrell, William E.; Fryer, Anthony A.; Carroll, William D.; Ismail, Khaled M. K.
Summary Antiepileptic drugs (AEDs) can lower maternal folate and increase maternal homocysteine levels, which are known to affect the methyl cycle and hence DNA methylation levels. The influence of in utero exposure to AEDs on fetal DNA methylation was investigated. Genome‐wide fetal epigenomic profiles were determined using the Infinium 27K BeadArray from Illumina (San Diego, CA, U.S.A.). The Infinium array measures approximately 27, 000 CpG loci associated with 14, 496 genes at single‐nucleotide resolution. Eighteen cord blood samples (nine samples from babies exposed to AEDs and nine controls) from otherwise uncomplicated pregnancies were compared. Unsupervised hierarchic clustering was used to compare the calculated methylation profiles. A clear distinction between the methylation profiles of samples from babies exposed to AEDs in utero compared with controls was detected. These data provide evidence of an epigenetic effect associated with antenatal AED and high‐dose folate supplementation during pregnancy. The differences in fetal DNA methylation of those exposed to AEDs shows that a genome‐wide effect of methylation is evident. In addition, the epigenetic changes observed appear to be, in this limited sample, independent of extremes of birth weight centiles. These preliminary data highlight possible mechanisms by which AEDs might influence fetal outcomes and the potential of optimizing AED‐specific folate supplementation regimens to offset these effects.